Маловідомі джерела до історії “Великого терору” - Бажан, О.Г.; Золотарьов, В.А. (Сумський історико-архівний журнал, 2010)
The publication of the extracts from the certifying case of the official I. Dvorkin of Chernihiv NKVD regional department gives the opportunity of broadening the knowledge about the mechanism of putting mass terror into practice by Soviet punitive bodies and its social-political direction.